1961
DOI: 10.1144/gsjgs.117.1.0091
|View full text |Cite
|
Sign up to set email alerts
|

The Glacial Drifts of the Southern Part of the Shropshire-Cheshire Basin

Abstract: Official work on the Nantwich district (Sheet 122) showed t h a t the sequence of two boulder-clays with associated fluvioglacial deposits, previously recognized only in the northern part of the Shropshire–Cheshire basin, also extended into its centre. Subsequent private research has shown that this sequence may be distinguished throughout the whole basin and in a critical region beyond its south-eastern margin—in total an area exceeding 3000 square miles. The recognition of glacial lake features cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

1973
1973
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
0
27
2
Order By: Relevance
“…Peake argued that the Wrexham terrace was fed by meltwater draining down the Alyn Valley from the north. Poole and Whiteman (1961) suggested that the terrace was not a delta but part of an end moraine system extending from Wrexham to Ellesmere. Specifically, they suggested that the Middle Sands record the recession of the ice responsible for the deposition of the Lower Boulder Clay and that the Upper Boulder Clay recorded a later advance by the Irish Sea ice right up to the base of the Welsh upland massif.…”
Section: Welsh/english Borders and Cheshire-shropshire Lowlandsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peake argued that the Wrexham terrace was fed by meltwater draining down the Alyn Valley from the north. Poole and Whiteman (1961) suggested that the terrace was not a delta but part of an end moraine system extending from Wrexham to Ellesmere. Specifically, they suggested that the Middle Sands record the recession of the ice responsible for the deposition of the Lower Boulder Clay and that the Upper Boulder Clay recorded a later advance by the Irish Sea ice right up to the base of the Welsh upland massif.…”
Section: Welsh/english Borders and Cheshire-shropshire Lowlandsmentioning
confidence: 99%
“…8) variously named the "Wrexham-Ellesmere-Wem-Whitchurch-Woore Moraine" (e.g. Lewis, 1894;Pocock and Wray, 1925;Peake, 1961;Poole and Whiteman, 1961;Yates and Moseley, 1967), the "Middle Sands Moraine" by Poole and Whiteman (1961) and "Bar Hill-Whitchurch-Wrexham Moraine" by Boulton and Worsley (1965). Thomas (1989) (Thomas, 1985; see above) with those to the south of Ellesmere.…”
Section: Welsh/english Borders and Cheshire-shropshire Lowlandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with other terminal moraine complexes within the U.K. such as the Escrick (Cooper and Gibson, 2003); Cromer (Hart, 1990) and Bride (Thomas, 1984) have shown that it is one of the largest. A series of conflicting models have been proposed for the origin of the BHWWMC including: 1) ice stagnation during retreat (Jowett and Charlesworth, 1929;Worsley, 1970); 2) formation during a re-advance (Boulton and Worsley, 1965;Shotton, 1966;Yates and Moseley, 1967); 3) overriding of a pre-existing moraine ridge (Poole and Whiteman, 1961) and, 4) draping of glacial material over a bedrock ridge (McQuillin, 1964). However the mode of origin has remained uncertain, as the moraine's key characteristics have not been examined in detail, due to a lack of significant exposures from which the moraine's internal structure can be constrained.…”
Section: Introductionmentioning
confidence: 99%